Morphometric investigation of the effects of Azoxymethane, Diallyl disulfide and corn oil use on humerus and femur development in rats - Aydoğdu, Sedat (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
The study aimed to examine the effects of Azoxymethane (AOM), Diallyl Disulfide (DADS), and corn oil on the humerus and femur in rats. In the study, 40 male Wistar Albino rats, 12 weeks old, were used. The animals were divided into four different groups (Control, AOM, DADS and Corn oil). After the experimental period, all animals were anesthetized and sacrificed by cervical dislocation. Humerus and femur from long bones resected from all animal groups. The maximum length, proximal width, distal width, diaphysis diameter, cortex thickness and cavum medullare diameter of the bones were measured. After the morphometric measurements index 1, index 2, robusticity index, and bone weight/bone length index were calculated for the bones. No difference was observed in the morphometric measurements and indices performed on the humerus. A statistical difference in proximal width and robusticity index was detected between the groups in the femur. A difference was observed between the AOM group and the Control/corn oil groups in proximal width. A difference was detected between the AOM group and the Control group in the robustness index, and it was determined that AOM caused a decrease in density and strength in bones. It is thought that the findings obtained in this study will contribute to the evaluation of the effects of cancer research using AOM on bones in rats.